2009
DOI: 10.1080/02786820902810685
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Soot by Controlled Sulphuric Acid and Water Condensation—Mass and Mobility Relationship

Abstract: . To simulate atmospheric processing, combustion soot agglomerates were altered by sulphuric acid vapor condensation, relative humidity (RH) cycling, and evaporation of the sulphuric acid and water by heating. Primary investigated properties were particle mobility size and mass. Secondary properties, derived from these, include effective density, fractal dimension, dynamic shape factor, and the mass fraction of condensed material. A transformation of the soot particles to more compact forms occurs as sulphuric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
265
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(294 citation statements)
references
References 53 publications
23
265
6
Order By: Relevance
“…The decrease in diameter (longest projected area) of the soot particles from before to after scrubber is indicative of an increase in density. Pagels et al (2009) state that for water and sulfuric acid condensing on combustion soot, a mass increase of 2-3 times is needed for a transformation to spherical particles (fractal dimension approaching 3) with the same diameter. Following this line of thought, the particles observed in this study would not have increased in mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in diameter (longest projected area) of the soot particles from before to after scrubber is indicative of an increase in density. Pagels et al (2009) state that for water and sulfuric acid condensing on combustion soot, a mass increase of 2-3 times is needed for a transformation to spherical particles (fractal dimension approaching 3) with the same diameter. Following this line of thought, the particles observed in this study would not have increased in mass.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that material (probably due to fuel composition: sulfur content of 0.5% w/w to 0.75% w/w) had already condensed on particles before the scrubber, causing some change in morphology from fresh to partly compacted soot forms. Pagels et al (2009) observed that under atmospheric conditions, particles will be fully transferred to spherical droplets on a timescale of several hours. We think that in the condition of an EGR scrubber, where more water vapor is available, hygroscopic growth occurs in minutes, or even seconds.…”
Section: Discussionmentioning
confidence: 99%
“…A combined nano-scanning mobility particle sizer (SMPS) and standard SMPS was deployed to measure the particle size distributions. The size-resolved particle density and hygroscopicity were measured using an aerosol particle mass analyzer and a hygroscopic tandem differential mobility analyzer (43)(44)(45)). An Aerodyne highresolution time-of-flight aerosol mass spectrometer was used to measure the chemical compositions of submicron particles, with a collection efficiency of about 50% (29,46).…”
Section: Methodsmentioning
confidence: 99%
“…However, soot particles will become hydrophilic if water-soluble compounds, such as sulfuric acid or organics condense on the surface, and then collapse into a spherical shape when the relative humidity (RH) is increased (Zhang et al, 2008;Pagels et al, 2009). The effective density of coated and annealed soot increases, consistent with restructuring of the soot cores after they acquire sufficient fractions of coating material (Cross et al, 2010;Qiu et al, 2012;Saathoff et al, 2003;Pagels et al, 2009). The extent of 30 restructuring depends on the production conditions of the soot, as well as on the mass fraction and type of the coating material.…”
mentioning
confidence: 99%